2020
DOI: 10.1101/2020.08.29.272369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proximity labeling at non-centrosomal microtubule-organizing centers reveals VAB-10B and WDR-62 as distinct microtubule regulators

Abstract: SummaryReorganization of microtubules from the centrosome to non-centrosomal subcellular sites is central to cell differentiation. To identify components of non-centrosomal microtubule organizing centers in differentiated cells of a living organism, we developed the biotin ligase-based proximity labeling approach TurboID for use in C. elegans. We identified proteins proximal to the non-centrosomal microtubule minus end protein PTRN-1/Patronin at the apical membrane of epithelial cells, focusing on two conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
2
2
0
Order By: Relevance
“…Minor extensions of PKC-3 away from the apical surface were occasionally observed in Stage 4 and older AFD-1 gut(-) embryos (Fig. S5), similar to those observed in embryos with actin defects (Gobel et al, 2004;Ramalho et al, 2020;Sanchez et al, 2021;Sasidharan et al, 2018;Van Furden et al, 2004). Importantly, this result suggests that while AFD-1 may contribute to the assembly and movement of lateral puncta to the intestinal midline, other mechanisms are sufficient for local and global apical establishment.…”
Section: Different Apical and Junctional Proteins Play Different Roles In Global Apical Establishmentsupporting
confidence: 71%
See 2 more Smart Citations
“…Minor extensions of PKC-3 away from the apical surface were occasionally observed in Stage 4 and older AFD-1 gut(-) embryos (Fig. S5), similar to those observed in embryos with actin defects (Gobel et al, 2004;Ramalho et al, 2020;Sanchez et al, 2021;Sasidharan et al, 2018;Van Furden et al, 2004). Importantly, this result suggests that while AFD-1 may contribute to the assembly and movement of lateral puncta to the intestinal midline, other mechanisms are sufficient for local and global apical establishment.…”
Section: Different Apical and Junctional Proteins Play Different Roles In Global Apical Establishmentsupporting
confidence: 71%
“…We tagged endogenous PAR-1 with GFP and found that it localized to centrosomes during mitosis prior to Stage 1 (Data not shown) and occasionally at midbodies in Stage 1 embryos (Fig. 1E), consistent with the ability of PAR-1 to bind to microtubules and associate with microtubule-binding proteins (Sanchez (Cohen et al, 2004;Doerflinger et al, 2003;Sanchez et al, 2021). At Stage 1, PAR-1 localized weakly to plasma membranes (Fig.…”
Section: Apical and Basolateral Domains Are Established At Different Times And Through Different Routessupporting
confidence: 64%
See 1 more Smart Citation
“…However, the authors did not publish interactome or proteomic data for C. elegans. A recent study used TurboID to characterize the interactome of the microtubule-binding protein patronin, but ectopically overexpressed this fusion protein in the largest tissue of the animal, the gut, and did not seek to optimise the protocol (29).…”
Section: Apexmentioning
confidence: 99%